If it's not what You are looking for type in the equation solver your own equation and let us solve it.
k in (-oo:+oo)
3*(3-6*k) = 117 // - 117
3*(3-6*k)-117 = 0
3*(3-6*k)-117 = 0
-18*k-108 = 0
-18*k-108 = 0
-18*k-108 = 0 // + 108
-18*k = 108 // : -18
k = 108/(-18)
k = -6
k = -6
| 6(2-b)=-60 | | 7(3+6t)=105 | | 4(1n+8)=48 | | 3(-4n+10)=-78 | | 4(5+6b)=308 | | 2(-7x+10)=6 | | 3(2x+9)=87 | | 6(3-3x)=0 | | 7(3m+3)=0 | | 3(1b-5)=3 | | 4(1w+8)=64 | | 3(7n+5)=225 | | 6(2-d)=42 | | 4(6-4m)=8 | | 3(-2a-10)=-60 | | 4(10+7b)=-212 | | 7(1t+6)=14 | | 6(10+2x)=180 | | 2(1x+3)=8 | | 7(3-4x)-5(2x+8)=0 | | 4(6m+3)=-276 | | 6(4+7d)=192 | | 5(2a+8)=40 | | 3(-1a-1)=-33 | | 6(-7b-1)=288 | | 5(2x-3)-3(x-2)=0 | | 2(7k+2)=-52 | | 7(9+6a)=357 | | 6(-3x+2)=-78 | | 2(9+5w)=138 | | 2(2-5b)=104 | | 3(5b+1)=18 |